Infrarail 2001 developments in the railway industry. (Thomas Telford, 2001)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a meeting held at Wembley in September 2001.
Keywords: Railroads -- Congresses.; elektronické knihy; electronic books